Vosaroxin for acute myeloid leukemia - El-Amm, Joelle (2014)
The treatment of acute myeloid leukemia (AML) in adults has not significantly changed in the past five decades. Despite the availability of effective induction chemotherapy, most patients eventually relapse. Relapsed or refractory AML, and AML in patients 60 years of age and older are particularly difficult to treat and have poor prognosis hence the need for novel therapies. Vosaroxin is a novel first-in-class anticancer quinolone derivative that intercalates DNA and inhibits topoisomerase II. Vosaroxin was shown in preclinical studies to be a potent antileukemia agent with unique features that overcome common mechanisms of resistance to standard therapy. Vosaroxin as single agent or in combination with cytarabine showed promising tolerability and activity in Phase I and II studies. The combination of vosaroxin and cytarabine is currently being studied in the Phase III VALOR trial that will define the role of vosaroxin in first relapsed or refractory AML. This review summarizes the preclinical and clinical studies of vosaroxin in AML.